Mastery of language grammar among non-Malay students - Jamian, Abdul Rasid; Md Sabil, Azhar; Othman, Shamsudin; Zakaria, Nur Nabilah; Kaboodvand, Tahereh (Human Resource Management Academic Research Society, 2017)
This study targets to classify the level of mastery of the Malay language grammar of non - Malay students. Furthermore, this study explored the factors that influence on the mastery of Malay language. The survey method was used to distribute questionnaires among 100 Chinese students. The findings show that Chinese students are still weak in the knowledge of Malay language grammar (N= 1.96; SD= 0.46). This specifies that Chinese students are still incapable of producing good essays and are profoundly influenced by the mother tongue. Their roots are weak in Malay due to their attitude, lack of teaching aids, teachers' attitudes and parental attitudes. Therefore, all parties need to play a role in helping to improve the mastery of the Malay grammar of Chinese students. This helps them not to stay out of the lesson, especially in Malay language subjects.